The Introduction of the New Mongol Administrative, Economic and Political System in the Vilayet of Gourjistan in the Mid-13th Century. - Mkrtumyan, Lernik (History and Culture, 2025)
The article is devoted to the period immediately fter the conquest of Armenia and Transcaucasia and the cessation of revenues from plunder and robbery,when for the Mongols had to find a new way of obtaining a stable and permanent income. To this end, the Mongols established a system of state administration with a stable political and economic structure in the territories under their control, including the Caucasus and Armenia. The census of 1254 and the subsequent introduction of a heavy poll tax served this purpose. Guided by the principle of "divide and conquer", the Mongols granted the House of Orbelian of Syunik and the House of Yeranshaheek of Inner Khachen the status of Injou. In this way, they removed their lands from the Zakarian suzerainty. At the same time, a power struggle was developing in Transcaucasia between the great Khans of Karakorum and the Juchids of the Golden Horde. In this struggle, both sides relied on the Georgian-Armenian feudal nobility. As a result of this struggle, royal authority in Georgia was weakened. Both branches of the Zakarid family, the Vakhramids and the Yeransheekes of the Inner Khachen, were also weakened. On the contrary, the influence of the owner of Mahkaneberd, Sadun Artsrouni, and the Armenian branch of the Orbelians has increased.
Keywords: Mongol Empire; Gurjistan vilayet; North-West Armenia; Baskak; Argoun; koupchour; census; Zakarides; Smbat Orbelyan; Hassan-Jalal Dola